2021
DOI: 10.1038/s41419-021-03532-y
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: MYC-mediated upregulation of PNO1 promotes glioma tumorigenesis by activating THBS1/FAK/Akt signaling

Abstract: PNO1 has been reported to be involved in tumorigenesis, however, its role in glioma remains unexplored. In the present study, PNO1 expression in glioma from on-line databases, cDNA, and tissue microarrays was upregulated and associated with poor prognosis. PNO1 knockdown inhibits tumor cell growth and invasion both in vitro and in vivo; whereas PNO1 overexpression promoted cell proliferation and invasion in vitro. Notably, PNO1 interacted with THBS1 and the promotion of glioma by PNO1 overexpression could be a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…S4D ). AKT and ERK1/2 were downstream mediators of FAK pathway, and FAK/AKT/ERK1/2 axis is one of the focal adhesion pathways that are important for cell proliferation and motility [ 25 , 26 ]. Immunoblot findings revealed that p-AKT (Ser473) and p-ERK1/2(Thr202/Tyr204) proteins expression were obviously decreased in MEOX2 knockdown cells, while were significantly increased in MEOX2 overexpression cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S4D ). AKT and ERK1/2 were downstream mediators of FAK pathway, and FAK/AKT/ERK1/2 axis is one of the focal adhesion pathways that are important for cell proliferation and motility [ 25 , 26 ]. Immunoblot findings revealed that p-AKT (Ser473) and p-ERK1/2(Thr202/Tyr204) proteins expression were obviously decreased in MEOX2 knockdown cells, while were significantly increased in MEOX2 overexpression cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Bromodomain-4 protein (BRD4) positively regulates EZH2 transcription through Myc upregulation [ 56 ]. Myc activation was reported in glioblastoma progression, particularly in poor prognosis and therapy resistant-tumors [ 55 , 57 ]. EZH2 mediates proliferation, migration, and invasion in GBM.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, besides THBS1, DDIT4, TCL1A, and AREG might be biological markers in the prognosis of septic shock by acting via PI3K/Akt signaling pathway. Still, the role of THBS1 in the regulation of the PI3K-Akt signaling pathway in cancer is relatively well defined [34], but its role in sepsis remains to be determined.…”
Section: Discussionmentioning
confidence: 99%